Expression of the Arabidopsis Gene Akr Coincides with Chloroplast Development. - Zhang, H. (1994)
Reduced expression of a nuclear gene of Arabidopsis thaliana, Akr, results in the formation of chlorotic plants due to a block in the proplastid-to-chloroplast development pathway (H. Zhang, D.C. Scheirer, W. Fowle, H.M. Goodman [1992] Plant Cell 4: 1575-1588). In an effort to discern the function of the Akr gene product in chloroplast development, transgenic plants containing an Akr::[beta]-glucuronidase gene fusion were constructed to monitor the spatial and temporal patterns of Akr expression. Akr is expressed only in chloroplast-containing tissues and maximal expression occurs during the seedling stage, coincident with chloroplast development. This result is consistent with the hypothesis that Akr is required at an early stage of chloroplast development. The effects of an AKR deficiency on the expression of nuclear and plastid genes required for photosynthetic activity were also examined. Within chloroplast-deficient leaves of plants in which Akr expression is limited by the presence of Akr antisense transgenes or truncated Akr sense transgenes, mRNAs for the nuclear genes Cab2, Cab4, RbcS, and GapA are present at wild-type levels; similarly, levels of mRNAs for the plastid genes rbcL and psbA are not affected by the AKR deficiency. Thus, although expression of these photosynthetic genes is tightly coordinated with the development and maintenance of chloroplasts in wild-type plants, their expression is unaffected in AKR-deficient chlorotic leaves. Therefore, we propose that Akr functions in a pathway different from the one controlling the expression and regulation of the photosynthetic genes during chloroplast development, and at a specific developmental stage after the putative plastid factor is made.